Gem quality and archeological green 'jadeite jade' versus 'omphacite jade'1. (24th June 2014) - Coccato, Alessia; Karampelas, Stefanos; Wörle, Marie; van Willigen, Samuel; Pétrequin, Pierre; Ropret, Polonca; Madariaga, Juan Manuel
<x xml:space="preserve">Abstract</x> Raman spectroscopy was used for the characterization of seven gem quality green 'jade' samples and three green 'jade' samples of archaeological importance. The results were also compared with those acquired by other nondestructive techniques such as classical gemology, energy‐dispersive X‐ray fluorescence (EDXRF), ultraviolet‐visible‐near infrared (UV‐Vis‐NIR) in absorption, Fourier transform infrared spectroscopy (FTIR) in absorption and micro‐FTIR in reflectance. Five samples of gem quality and two samples of archaeological interest were found to be 'jadeite jade', whereas two samples of gem quality and one sample of archaeological interest were 'omphacite jade'. Raman spectroscopy is found to be the most efficient method for their characterization. The results were confirmed with EDXRF and micro‐FTIR in reflectance. Data acquired using classical gemology, UV‐Vis‐NIR absorption and FTIR absorption spectroscopy were similar on 'omphacite jade' and 'jadeite jade'. Copyright © 2014 John Wiley & Sons, Ltd.